Perlindungan Hukum Waris Anak Luar Kawin Dalam Masyarakat Hindu Lombok - Andy Gunawan; Sirajuddin Sailellah; Yuliasara Isnaeni (Postgraduate of Jayabaya University, 2018)
In the division of inheritance, generally will be shared equally, but unlike inheritance in the Hindu community of Lombok Mataram in Cakranegara subdistrict. The method used is the normative law supported by empirical law. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In addition, primary data is also used as supporting material of secondary data law. For data analysis done with qualitative juridical. Customary law comes from religious law, but there is a contradiction where according to Hindu law an outsider cannot be acknowledged and will not get inherited, but in the subdistrict of cakranegara the child outside marriage is not necessary to adopt the child will immediately be regarded as a legitimate child and obtain inheritance the same as a legitimate child as long as there is no other marriage.